Gastric Malignant Peripheral Nerve Sheath Tumor in Type 1 Neurofibromatosis - Hwang, Hyun Seung; Jeong, Yun Jin; Nam, Kyung Han; Oh, Sung Jin; Park, Yong Eun (The Korean journal of gastroenterology, 2022)
Gastric malignant peripheral nerve sheath tumors (MPNSTs) are extremely rare spindle cell sarcomas that arise within the peripheral nerves of the gastrointestinal tract. MPNST can present as a mass that may or may not be accompanied by obstruction or bleeding. Type 1 neurofibromatosis (NF) is an autosomal dominant genetic disorder with an incidence of 1 in 2,500-3,000. Plexiform neurofibromas in Type 1 NF can undergo a malignant transformation to MPNSTs. Approximately half of the incidence of MPNST is associated with the NF-1 gene. MPNST behaves aggressively, and radical excisional surgery is important for treatment. Recurrence and metastasis are significant, even after a radical excision. Despite multidisciplinary treatment, the five-year survival rate is only 30-50%. This paper reports the case of a 47-year-old man with Type 1 NF who presented with hemorrhage of a gastric subepithelial lesion. He underwent surgery under the suspicion of a gastrointestinal stromal tumor, but it was diagnosed as MPNST after confirming the histopathological appearance and immunohistochemical profiles. In addition, the large mass invaded the spleen and diaphragm. Radical surgery was performed, and additional chemotherapy was administered. This paper reports the experience of a patient with NF 1 with advanced MPNST discovered due to a subepithelial lesion.